Direct homophilic interaction of LAMP2A with the two-domain architecture revealed by site-directed photo-crosslinks and steric hindrances in mammalian cells. Issue 12 (2nd December 2021) - Terasawa, Kazue; Kato, Yuji; Ikami, Yuta; Sakamoto, Kensaku; Ohtake, Kazumasa; Kusano, Seisuke; Tomabechi, Yuri; Kukimoto-Niino, Mutsuko; Shirouzu, Mikako; Guan, Jun-Lin; Kobayashi, Toshihide; Iwata, Takanori; et al.
ABSTRACT: LAMP1 (lysosomal-associated membrane protein 1) and LAMP2 are the most abundant protein components of lysosome membranes. Both LAMPs have common structures consisting of a large lumenal domain composed of two domains (N-domain and C-domain, which are membrane-distal and -proximal, respectively), both with the β-prism fold, a transmembrane domain, and a short cytoplasmic tail. LAMP2 is involved in various aspects of autophagy, and reportedly forms high-molecular weight complexes at the lysosomal membrane. We previously showed that LAMP2 molecules coimmunoprecipitated with each other, but whether the homophilic interaction is direct or indirect has remained to be elucidated. In the present study, we demonstrated the direct homophilic interaction of mouse LAMP2A molecules, using expanded genetic code technologies that generate photo-crosslinking and/or steric hindrance at specified interfaces. Specifically, the results suggested that LAMP2A molecules assemble by facing each other with one side of the β-prism (defined as side A) of the C-domains. The N-domain truncation, which increased the coimmunoprecipitation of LAMP2A molecules in our previous study, permitted the nonspecific involvement of both sides of the β-prism (side A and side B). Thus, the presence of the N-domain restricts the LAMP2A interactions to side A-specific. The truncation of LAMP2A impaired the recruitment of GAPDH (a CMA-substrate) fused to the HaloTag protein to the surface of late endosomes/lysosomes (LE/Lys) and affected a process that generates LE/Lys. The present study revealed that the homophilic interaction of LAMP2A is direct, and the side A-specific, homophilic interaction of LAMP2A is required for the functional aspects of LAMP2A. Abbreviations: Aloc-Lys: N ε -allyloxycarbonyl-l -lysine; CMA: chaperone-mediated autophagy; FFE: free-flow electrophoresis; GAPDH-HT: glyceraldehyde-3-phosphate dehydrogenase fused to HaloTag protein; LAMP1: lysosomal-associated membrane protein 1; LAMP2A: lysosomal-associated membrane protein 2A; LBPA: lysobisphosphatidic acid; LE/Lys: late endosome/lysosomes; MEFs: mouse embryonic fibroblasts; p Bpa: p -benzoyl- l -phenylalanine